PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA WISATA (Studi Pada Desa Wisata Gamtala, Kabupaten Halmahera Barat) - Sukur Suleman; Christina Kahumata (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2020)
Development carried out by the government requires the participation of the village community, including tourism development. The focus of this research is community participation in the development of a tourist village, a study in the tourist village of Gamtala, West Halmahera Regency. The method used in this research is qualitative with a descriptive approach. Data collection techniques used were interviews, observation and documentation. The data analysis technique is carried out with an interactive model with the stages of data reduction, data presentation and then drawing conclusions. The results of the research show that the village government of Gamtala has made the village a tourist destination with the concept of a tourist village. To build a tourist village, the village government tries to encourage community involvement and participation. However, community participation in the development of this tourist village was not optimal, because the communication and coordination carried out by the government was poor. As a result, not all people are aware of the government program regarding the development of the tourist village.